2012
DOI: 10.5051/jpis.2012.42.6.256
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis and treatment of periodontitis-mimicking actinomycosis

Abstract: PurposeActinomycosis is an uncommon chronic granulomatous disease that presents as a slowly progressive, indolent, indurated infiltration with multiple abscesses, fistulas, and sinuses. The purpose of this article is to report on a case of actinomycosis with clinical findings similar to periodontitis.MethodsA 46-year-old female presented with recurrent throbbing pain on the right first and second molar of the mandible three weeks after root planing. Exploratory flap surgery was performed, and the bluish-gray t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…13 In a recent case reports, Rodan and Nam Ryang Kim reported presence of actinomycosis in periodontally affected sites. 14,15 In the present case, the Actinomyces species affected tooth was periodontally and endodontically involved and patient showed poor oral hygiene which The treatment for actinomycosis includes combination of surgical debridement of the involved tissues and the prolonged administration of antibiotics. The traditional treatment is usually a long-term course of penicillin, which includes 1 month of intravenous penicillin G (1 to 6 million units per day for cervicofacial type and 10 to 20 million units per day for thoracic and abdominal type), followed by weeks to months of oral penicillin.…”
Section: Discussionmentioning
confidence: 70%
“…13 In a recent case reports, Rodan and Nam Ryang Kim reported presence of actinomycosis in periodontally affected sites. 14,15 In the present case, the Actinomyces species affected tooth was periodontally and endodontically involved and patient showed poor oral hygiene which The treatment for actinomycosis includes combination of surgical debridement of the involved tissues and the prolonged administration of antibiotics. The traditional treatment is usually a long-term course of penicillin, which includes 1 month of intravenous penicillin G (1 to 6 million units per day for cervicofacial type and 10 to 20 million units per day for thoracic and abdominal type), followed by weeks to months of oral penicillin.…”
Section: Discussionmentioning
confidence: 70%
“…The typical mass at the angle of the jaw (lumpy jaw), draining sinuses with granules from discharging ulcers, abscess formation, fistulae and fibrous tissue formation are not always present, as typified by our cases. In a similar fashion, Kim et al reported a presentation of actinomycosis mimicking periodontitis without the other classic features associated with cervicofacial actinomycosis [ 7 ].…”
Section: Discussionmentioning
confidence: 97%
“…The isolation of Actinomyces spp. from blood culture is traditionally regarded as clinically significant [61]. However, the possibility of contaminants does exist [62].…”
Section: Discussionmentioning
confidence: 99%